2007
DOI: 10.2353/ajpath.2007.061004
|View full text |Cite
|
Sign up to set email alerts
|

Direct Involvement of Breast Tumor Fibroblasts in the Modulation of Tamoxifen Sensitivity

Abstract: Using contact-dependent three-dimensional coculture systems and serum-free conditions, we compared the ability of estrogen receptor (ER)-␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 51 publications
0
82
0
Order By: Relevance
“…In 1990, Teicher and colleagues proposed that something other than the inherent properties of tumor cells must affect the ability of these cells to resist cytotoxic drugs (38). Since then, several studies have shown that fibroblasts can induce resistance to various anticancer treatments, such as tamoxifen in the treatment of breast cancer (28,39), gemcitabine and radiotherapy in the treatment of pancreatic adenocarcinoma (26), and paclitaxel in the treatment of non-small cell lung cancer (30). Conversely, fibroblasts may also sensitize tumor cells to therapy as was shown for RAF and MEK1 inhibitors in breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1990, Teicher and colleagues proposed that something other than the inherent properties of tumor cells must affect the ability of these cells to resist cytotoxic drugs (38). Since then, several studies have shown that fibroblasts can induce resistance to various anticancer treatments, such as tamoxifen in the treatment of breast cancer (28,39), gemcitabine and radiotherapy in the treatment of pancreatic adenocarcinoma (26), and paclitaxel in the treatment of non-small cell lung cancer (30). Conversely, fibroblasts may also sensitize tumor cells to therapy as was shown for RAF and MEK1 inhibitors in breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…CAFs provide protumorigenic signals that lead to increased tumor growth via the stimulation of tumor cell proliferation and angiogenesis as well as the formation of metastases by the enhancement of the migratory and invasive potential of the tumor cells (18)(19)(20)(21)(22)(23)(24)(25). As a number of publications suggest that CAFs could also modulate the drug sensitivity of cancer cells (26)(27)(28)(29)(30)(31)(32)(33)(34), this study was undertaken to evaluate the influence of CAFs on the cetuximab response in HNSCC cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to NAF, CAF exhibit an increased production of type-specific collagens and a variety of growth factors and proteases (Tlsty 2001). As a consequence, CAF enhance tumor growth, facilitate metastasis, mediate resistance to chemotherapy and hormonal therapies, and promote neoangiogenesis (Horgan et al 1987;Noel et al 1993;Muerkoster et al 2004;Orimo et al 2005;Shekhar et al 2007;Ostman and Augsten 2009). The CAF phenotype is stimulated by paracrine signaling between cancer cells and resident fibroblasts or bone marrow-derived mesenchymal stem cells and is known to be induced by PDGF and Hedgehog ligand, both of which require PC for regulated signaling (Shao et al 2000;Ishii et al 2003;Kalluri and Zeisberg 2006;Zeisberg et al 2007;Bailey et al 2008;Ostman and Augsten 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblasts form the source of many well-known tumorpromoting factors, including EGF, TGFβ or HGF. Previous studies have demonstrated that myofibroblasts affect sensitivity of malignant cells to chemo-or radiotherapy (17,18) and have a direct pro-metastatic effect (19).…”
Section: Discussionmentioning
confidence: 99%